The influences of holmium on the solidification, microstructure and mechanical properties of elektron 21 magnesium alloy - Shahizan, Nurul Raihan (2018)
The solidification parameter of Elektron 21 magnesium alloys with various Ho concentrations were investigated using computer-aided cooling curve thermal analysis system, and the solidification microstructure and phase constitution of the investigated alloys were characterized by SEM, EDX, and XRD. The mechanical properties were also investigated comparatively. The Ho was selected due to the ability to develop new intermetallic phases together with Mg and have a positive potential to reflect the properties of Mg alloys. As the outcome from this study, the cooling parameter of Elektron 21 with lower addition Ho content, the nucleation and growth temperature of α-Mg in Elektron 21 magnesium alloy decreased, where the Ho changed the solution degree of Zn, which resulted in refinement of microstructure. The results of solidification parameters showed the addition of 0.083 and 0.16 wt. % Ho cause a decrease of the solidification temperature alloys, which lead to the grain size about 64.0 %, which being a most effective addition. The microstructure of the result indicated that the intermetallic phases in the Elektron 21 cast alloy consisted mainly of α-Mg matrix, Mg12Nd, Mg41Nd5, Mg3Gd and Mg3Nd phase. The lower addition of Ho consists of Mg-Zn-Ho phase appears in the cast alloys. However, after adding 0.5 to 3.0 wt. % Ho, the Mg-Zn-Ho phase was suppressed and the phase has earlier been mixed Mg2Ho and Mg3Ho phase. Moreover, the addition of 0.083 wt. % of Ho exhibited an excellent improvement of ultimate tensile strength, yield strength and hardness of 139.7 MPa, 105.62 MPa and 103.52 Hv, respectively. The solidification, microstructure and mechanical properties of Elektron 21 magnesium alloys influenced by the Ho concentration in the magnesium alloys; Elektron 21 with 0.083 wt.% Ho exhibited the refinement of microstructure and displayed the best properties compared to other alloys.